Małgośka and Damą być, on the German translation of selected texts by Agnieszka Osiecka - Tomecka, Magdalena (Acta Universitatis Lodziensis. Folia Germanica, 2023)
The article discusses translation strategies for the lyrics of Agnieszka Osiecka’s songs, highlighting the challenges associated with transferring verbal-musical content into another language. The article emphasizes that literal translations may not always preserve the original function of the song, and the key decision for the translator becomes the choice between a formal and dynamic approach. The author points out two levels of impact that songs have on the listener: a sensory level, related to sound and melody, and a cognitive level, associated with understanding and interpreting the lyrics. Hence, successful translation of songs requires consideration of both these aspects.